NO2 Gas Sensing Properties of Carbon Films Fabricated by Arc Discharge Methane Decomposition Technique - Elnaz Akbari; Zolkafle Buntat; Syed Muhammad Zafar Iqbal; Zulkifli Azman; Norain Sahari; Zainuddin Nawawi; Muhammad Irfan Jambak; Muhammad Abu Bakar Sidik (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this work, a set of experiments has been conducted using arc discharge Methane decomposition attempting to obtain carbonaceous materials (C-strands) formed between graphite electrodes. The current-voltage (I-V) characteristics of the fabricated C-strands have been investigated in the presence and absence of two different gases, NO2 and CO2. The results reveal that the current passing through the carbon films increases when the concentrations of gases are increased from 200 to 800 ppm. This phenomenon is a result of conductance changes and can be employed in sensing applications such as gas sensors.